Characterization and studies of enzymes and metabolites of antagonistic bacteria against pathogenic fungus; phytophthora capsici - Syaza, Binti Ahmad Hashim (unimas, 2014)
Phytophthora blight is highly destructive disease of plant especially in pepper and cucurbits. The disease caused by the water mold or also known as oomycete pathogen Phytophthora capsici can be overcome by using antagonist bacteria as the alternative method. In order to select the potential biological control agents (BCAs) for controlling the disease, the screening of selected bacterial strains; Pseudomonas spp. and Bacillus spp. were conducted by using a dual-culture assay with the P. capsici whether with single or mixed of two potential antagonistic bacterial strain. The screening procedure which consists of antagonism test will detect the presence of inhibition zones and later the production of lytic enzymes and secondary metabolite with the presence of antibiotic will be assessed in vitro. The combination strain of both bacteria had the strongest activities against the P. capsici due to the broad range and different modes of action of the biocontrol agents